2020
DOI: 10.1007/s10198-019-01138-y
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness and budget impact of the microprocessor-controlled knee C-Leg in transfemoral amputees with and without diabetes mellitus

Abstract: Background The safe use of a prosthesis in activities of daily living is key for transfemoral amputees. However, the number of falls varies significantly between different prosthetic device types. This study aims to compare medical and economic consequences of falls in transfemoral amputees who use the microprocessor-controlled knee joint C-Leg with patients who use non-microprocessor-controlled (mechanical) knee joints (NMPK). The main objectives of the analysis are to investigate the costeffectiveness and bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…Although falls in people with lower-limb amputations are considered major health events and receive the attention of public health researchers, current health technology assessments rely on a limited knowledge base. 55–57 The present study assessed the safety of prosthetic knees grouped into 4 categories. The evidence was based on more than 30 different knee models ( Suppl.…”
Section: Discussionmentioning
confidence: 99%
“…Although falls in people with lower-limb amputations are considered major health events and receive the attention of public health researchers, current health technology assessments rely on a limited knowledge base. 55–57 The present study assessed the safety of prosthetic knees grouped into 4 categories. The evidence was based on more than 30 different knee models ( Suppl.…”
Section: Discussionmentioning
confidence: 99%
“…Cost-effectiveness analyses, which compare treatments and their relative costs and outcomes, enable funders, governments and health care professionals and institutions, to make informed decisions about the care that is provided within funding constrained health care systems. 7 Unfortunately, the clinical evidence relating to most P&O interventions is lacking or is not of high quality. The highest evidence comes from meta-analyses of RCTs (Level 1), followed by at least one RCT (Level 2), quasi experimental designs (Level 3) and so on, and the majority of clinical research studies involving P&O interventions fall in the latter categories.…”
Section: Quality Effectiveness Validitymentioning
confidence: 99%
“…Interestingly, neither the effects of mortality nor the costs and health consequences due to falls were included in cost-effectiveness analyses until recently. 12 , 13 …”
Section: Introductionmentioning
confidence: 99%
“…They found that the clinical and economic benefits of MPKs were comparable with other reimbursed technologies in the United States. 12 Kuhlmann et al 13 extended this modeling strategy to apply both a cost-efficacy and budget-impact analysis on the use of MPKs in patients with or without diabetes mellitus (DM) in a German context. The predicted reduction in fall-related hospitalizations and deaths in individuals older than 40 years, who received an MPK, indicated health and economic benefits for individuals both with and without DM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation